Recent advances in analytical calibration with multi-way data - Olivieri, Alejandro Cesar (2012)
This critical review discusses the advances which have taken place in recent years in the field of multi-way instrumental data, i.e., data that can be arranged into a mathematical object of at least three ways (when they are measured for a group of samples). Particular focus is directed towards research works describing quantitative analytical calibrations. The development of data processing algorithms and the estimation of figures of merit are reviewed, along with the progress in the experimental generation of new three-, four- and five-way data of spectroscopic, chromatographic and electrochemical origin.